Inovasi Hijau, Umur Top Management, dan Profitabilitas: Studi pada Perusahaan Listrik - Putro, Rachmadi Kusentyo; Lubis, Arief Wibisono (Universitas Islam Kadiri, 2023)
The matter of climate change is progressively emerging as a worldwide preoccupation. Companies must innovate in order to overcome this challenge and simultaneously sustain their profitability. The future trajectory of a company is heavily contingent upon the extent to which its leaders actively pursue and implement innovative practices. This study seeks to examine the correlation between green innovation, the age of senior management, and profitability in electricitiy companies, which are the primary contributors to carbon emissions. Utilizing panel data regression analysis with secondary data spanning from 2013 to 2022, this study reveals that green process innovation exerts a noteworthy influence on return on assets (ROA). Furthermore, the age of top management acts as a moderating factor in the association between green process innovation and ROA. However, green product innovation does not exert a substantial influence on profitability. This study addresses the lack of research conducted on electricity comapnies, providing valuable insights for corporate stakeholders who are contemplating investments in green innovation and taking age into account when choosing top management. To enhance the academic rigor of this study, other factors pertaining to top management characteristics, such as educational background and diversity of the top management team, can be used.